Factores Psicosociales y Conductas Delictivas en Adolescentes: Revisión Sistemática - Loor Vélez, Mayerli Aracely (2024)
Delinquent behavior in adolescents is a public health problem with a global and timeless scope that has generated growing social concern considering the impact caused to the physical and mental health of the adolescent and those affected. Thus, numerous studies have pointed out the importance of psychosocial factors in the development and maintenance of this type of behavior in this age population; in light of this, the present research aims to determine the scientific evidence on psychosocial factors and delinquent behavior in adolescents; Consequently, a systematic review was carried out with a descriptive and cross-sectional approach, covering scientific articles published between 2014 and 2024 in the Dialnet, Scielo, Redalyc and Pubmed databases. After applying the selection criteria and being evaluated in terms of their design and results, 28 scientific articles were chosen as a representative sample of the research that led to obtaining the results which show that the psychosocial factors with the greatest incidence in delinquent behavior in adolescents are the consumption of alcohol and other substances and family dysfunction, being more prevalent in men than in women; Likewise, vandalism is one of the most common delinquent behaviors, followed by addictive behavior to substances, both as a behavior and as a psychosocial risk factor. In conclusion, psychosocial factors have become a central axis for the development of behaviors, whether adaptive or not, which makes their analysis a key reference point for the prevention and intervention of this phenomenon in vulnerable populations, such as adolescents